Manifestations of the Historian’s Presence in Two Historical Texts of the Safavid Era - Arezu Pooryazdanpanah Kermani (تاریخ ادبیات, 2023)
Historiography is one of the important branches of Islamic sciences which received great attention and success in the Safavid era. The presence of the historian in the text is one of the challenging issues of traditional and modern historiography, and two different views have been proposed in connection with it. The absence of the historian in the text and having an impartial position is one of the principles that is emphasized in traditional historiography; on the other hand, in modern historiography, historians are considered to have a serious and decisive role in the analysis of historical events. Studying a number of traditional historical books reveals that there are cases of the historian’s presence in the text, which violates the principle of the absence of the historian. This research seeks to investigate and evaluate the effects of the presence of historians in the historical books and how they position themselves by applying an analytical-descriptive method to two history books, Tarikh-e Alam-ara-ye Abbasi and Ahsan al-Tawarikh. The findings of the research indicate that the presence of the historian in the cited works is attested in the following forms: the historian referring to himself, having a biased view by employing positive and negative adjectives, describing the character of friends and enemies, rhetoric and the use of literary sentences, citing poems, referring to verses and hadiths, and using prayer expressions. Although Hasanbeg Rumlu and Skanderbeg Munshi are two contemporary historians who have recounted the same events in their works, the presence of Hasanbeg Rumlu in the text is far less than that of Skanderbeg Munshi and his position is more neutral.